Equilibrium of Faith and Logic: Integrating Islamic Moral Values and Mathematics Education in Various Contexts - Nurhikmah; Ibnu Imam Al Ayyubi; Eko Prayetno; Desti Jamaliah; Nabila Mumtazah (International Journal of Education Management and Religion, 2024)
The integration of Islamic moral values into mathematics education aims to create a balance between faith and logic, ensuring that learning is not solely focused on intellectual aspects but also on the development of noble character. This study seeks to explore the impact of this integrative approach on students' learning motivation, conceptual understanding, and moral value formation.Integrating Islamic values into mathematics education is challenging due to teachers' limited understanding of the connection between these values and mathematical concepts, insufficient resources, and students' lack of perceived relevance, which affects motivation.Time constraints and the need for institutional support further complicate this integration.Solutions include professional training for teachers, development of relevant materials, collaboration among educators, innovative teaching methods like project-based learning, and community involvement. Regular evaluations and feedback can enhance teaching strategies, fostering a generation that is academically skilled and morally grounded. The findings indicate that incorporating Islamic values such as honesty, justice, and responsibility into mathematics education enhances students' awareness of the real-life relevance of mathematics. Teaching methods such as case studies, project-based learning, and group discussions that link mathematics to Islamic values, such as zakat calculations and resource management, train students to think critically and make decisions based on ethical principles. Moreover, collaboration between mathematics teachers and Islamic education (PAI) teachers is a key factor in creating meaningful learning experiences. Despite challenges like additional time required for material preparation, this approach proves effective in shaping a generation that is not only academically proficient but also morally upright.